The Effect of Mas Card to Increase the Attractiveness of Learning English for Senior High School Students - Ari Abram; Eva Dwiyanti; Rafli Maulana Nugraha; Diane Harlisa Saraswati (Candradimuka: Journal of Education, 2023)
According to the online site nippon.com, English is the 5th most disliked subject by students. In contrast, mathematics is in the first position in the category of the least preferred subject (24.0%) but remains in the first position in the category of the most preferred subject (25.1%). Therefore, in fostering a sense of fun in English lessons, we introduce the MAS Card (Make A Sentence Card) as one of the media for English educational games. The MAS Card was created by Ari Abram, a student at Indraprasta University majoring in English education, the purpose of making this educational game is so that students can learn tenses in English and form sentences in a more fun way. This study has a verification purpose, to prove that the MAS Card can be used as a tool to foster a sense of pleasure in learning English among junior high school students, and to see how effective the MAS Card is in fostering interest in English lessons among junior high school students. This study uses a qualitative descriptive method, data will be collected through questionnaires that need to be filled out by students/participants to produce facts as they are using grounded theory. the results of this study will be presented in the form of oral data with a regular variable scale. To be able to show how much influence the MAS Card has in increasing the pleasure of learning English in junior high school students.